Analisis Faktor Penyebab Rendahnya Minat Belajar Siswa Terhadap Mata Pelajaran Matematika di MTs Ulul Albab - Cep Bambang Firdaus (Journal on Education, 2019)
This study aims to analyze the factors that cause low interest in students' learning in mathematics at MTs Ulul Albab. The method used in the research is the survey method. The research technique was carried out by distributing questionnaires which were then analyzed descriptively. Questionnaire consists of 24 items related to 1) feelings (11 questions), 2) attention in learning (5 questions), and 3) interest in the material and the teacher (8 questions), with 2 alternative answers to the questionnaire namely "Yes" and "No". The population of this study were all MTUL Ulul Albab students, while the sample was 60 students from various grade levels, consisting of 30 VII grade students, 30 VIII grade students, and 30 IX grade students. The results showed that the causes of low student learning interest in mathematics subjects were influenced (41.53%) at a moderate level enough to determine the low interest in learning mathematics, this condition is expected to increase again for the future